FACTORS AFFECTING ANXIETY OF BREAST MILK IN BREASTFEEDING MOTHERS : SCOPING REVIEW: Anxiety; Breastfeeding, breastfeeding mothers - Wulan Wijaya Wulan; Henni Febriawati (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Anxiety before and after childbirth can interfere with maternal function and mother-infant behavior including breastfeeding. Exclusive breastfeeding is breastfeeding alone without any additional food for 6 full months. Not all mothers give exclusive breastfeeding to their babies. This is influenced by various anxiety factors such as not initiating breastfeeding, breastfeeding duration. In this study using a scoping review methodology. This study combines knowledge and information related to current assumptions regarding the factors that influence exclusive breastfeeding. This study emphasizes breastfeeding anxiety factors such as breastfeeding initiation, breastfeeding duration and identifies 8 articles from a total of 8 articles, which were reviewed and summarized in a narrative manner. The findings of this study indicate that anxiety is the main factor for optimal breastfeeding. This research is expected to improve outcomes, and can be used as input for policy makers, health workers and service users.